Biomechanics of cross country skiing, from single segment to whole body movement - Pellegrini, B.; Zoppirolli, C.; Bortolan, L.; Schena, F. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Movement analysis of cross-country ski techniques has always been of great importance due to its influence on skiing performance. Understanding how a skier moves through the space involves measuring and analyzing a great number of parameters describing linear and angular motion, velocity and acceleration of many body segments. Researchers have chosen different way to accomplish this task.